IMPEACHMENT DALAM SISTEM PRESIDENSIAL: KAJIAN TEORITIK DAN NORMATIF DI INDONESIA SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR 1945 - Arry "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indonesia follows presidensial's system, where one of this system applies to mark sense impeachment to President. Constitution 1945 have experienced 4 (four) changed time, where is constitutions changed afters 1945 MPR is not again State supreme institutes where MPR no longer can lift and memberhentikan is Presidents. In contrast to before constitution amendment 1945 MPR constitute States supreme institutes MPR can lift and memberhentikan is Presidents. Since process impeachment President before amendment did by politics institute in this case the interesting institutes is DPR and MPR on a basic favors or bad blood to Presidena no ala order alae rinci hits basics, youngness processes President cessation as Soekarno's case and Abdurrahman Wahid.After amends therefore at manages procedure impeachment President and any kind President cause can at impeachement and involves jurisdiction institute in processes impeachment in this case MK. It aims as to establish check and balance in Indonesian State. Even decision a stop to process impeachment President is put hand out by MPR via voting (majority voice take). There is institute even that engages in to process impeachment Afters president amends Constitution 1945 be, DPR, MK, and MPR.Key word: President, Impeachment, Mechanism And State Institute.